2018
DOI: 10.1097/cad.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and doxorubicin resistance in cancer

Abstract: Doxorubicin (DOX), also known as adriamycin, is a DNA topoisomerase II inhibitor and belongs to the family of anthracycline anticancer drugs. DOX is used for the treatment of a wide variety of cancer types. However, resistance among cancer cells has emerged as a major barrier to effective treatment using DOX. Currently, the role of autophagy in cancer resistance to DOX and the mechanisms involved have become one of the areas of intense investigation. More and more preclinical data are being obtained on reversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(109 citation statements)
references
References 101 publications
2
107
0
Order By: Relevance
“…[36,37] Notably, autophagy plays a role in cancer resistance to chemotherapy and modulation of its components may restore drug sensitivity. [38] Chloroquine and hydroxychloroquine…”
Section: ]mentioning
confidence: 99%
“…[36,37] Notably, autophagy plays a role in cancer resistance to chemotherapy and modulation of its components may restore drug sensitivity. [38] Chloroquine and hydroxychloroquine…”
Section: ]mentioning
confidence: 99%
“…The high expression of ATG5 is closely related to the poor prognosis and drug resistance of gastric cancer [19]. It has been found that the disease-free survival rate and the overall survival rate of patients in the Beclin 1 high expression group are significantly increased [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that autophagy protein is closely related to the prognosis of GC patients. The high expression of ATG5 is closely related to the poor prognosis and drug resistance of gastric cancer [19]. It has been found that the disease-free survival rate and the overall survival rate of patients in the Beclin 1 high expression group are signi cantly increased [20].…”
Section: Discussionmentioning
confidence: 99%